(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the reality of governance in the Libyan tourism sector and its role in enhancing sustainability and administrative efficiency amid institutional and organizational challenges. Despite Libya’s rich natural and cultural tourism resources, weak infrastructure, overlapping authorities, and the absence of strategic planning limit sector performance. The study highlights that applying good governance principles—such as transparency, accountability, participation, and justice—represents a key approach to achieving sustainable tourism development and improving administrative efficiency. It also emphasizes the importance of digital transformation, legislative reform, human capacity building, and institutional restructuring. The research concludes that strengthening governance contributes to enhancing the competitiveness of Libyan tourism at both local and international levels while balancing economic growth with environmental and cultural preservation.